2017
DOI: 10.1002/ejic.201700096
|View full text |Cite
|
Sign up to set email alerts
|

The Crystal Structure of Nitridomagnesogermanate Ba[Mg3GeN4]:Eu2+ and Theoretical Calculations of Its Electronic Properties

Abstract: Nitridomagnesogermanate Ba[Mg3GeN4]:Eu2+ was synthesized by the NaN3 route in weld‐shut tantalum ampules by reaction of the elements in molten sodium with NaN3 as nitrogen source at 780 °C. The crystal structure was solved and refined on the basis of single‐crystal X‐ray diffraction data. Ba[Mg3GeN4]:Eu2+ crystallizes in the UCr4C4 structure type [space group I4/m (no. 87), a = 8.3921(12), c = 3.4813(7) Å, Z = 2] and exhibits a highly condensed anionic network made up of statistically disordered (Mg/Ge)N4 tetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 56 publications
(103 reference statements)
0
5
0
Order By: Relevance
“…[12][13][14] Furthermore, experiments introducing Ga and Ge into tetrahedra network structuresr esulted in part in luminescenceu pon Eu 2 + -dopingw ith poor QE due to small band gaps. [15][16][17] Promising large band gaps are again predicted when Be is included in tetrahedral coordination in highly condensed crystal structures. Due to the strong covalent character of Beligand bonds that are comparable to Al-and Si-ligand bonds, rigid network structures allowing narrow-band emission upon RE-doping could be accessible.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…[12][13][14] Furthermore, experiments introducing Ga and Ge into tetrahedra network structuresr esulted in part in luminescenceu pon Eu 2 + -dopingw ith poor QE due to small band gaps. [15][16][17] Promising large band gaps are again predicted when Be is included in tetrahedral coordination in highly condensed crystal structures. Due to the strong covalent character of Beligand bonds that are comparable to Al-and Si-ligand bonds, rigid network structures allowing narrow-band emission upon RE-doping could be accessible.…”
Section: Introductionmentioning
confidence: 93%
“…Latest investigations on nitridophosphate materials showed that structures built of condensed PN 4 tetrahedra are promising solid‐state phosphors . Furthermore, experiments introducing Ga and Ge into tetrahedra network structures resulted in part in luminescence upon Eu 2+ ‐doping with poor QE due to small band gaps …”
Section: Introductionmentioning
confidence: 99%
“…In addition, the corrosion resistant niobium and tantalum ampoules also provide a mechanically robust reactor, [43] where highly active sodium azide is commonly used as a nitrogen source. The asprepared nitrides include group (II) (Mg, Ca, Sr and Ba) nitrides (Figure 5a) [44][45][46] and group (III) nitrides, such as GaN3 [47] and Al2N4, [48] with doped lanthanide ion. Typical phosphides include zinc ( Figure 5b) [49][50][51] and lanthanum phosphides.…”
Section: Conceptmentioning
confidence: 99%
“…In contrast, smaller cations such as lithium, magnesium and 3 d transition metals are typically coordinated tetrahedrally. These smaller cations may share a crystallographic site with germanium(IV) atoms, for example in the nitridogermanates BaMg 3 GeN 4 and Ca 5 Mg 4 Ge 3 N 10 . The semiconductor material ZnGeN 2 has been reported in an early publication to crystallize in the Wurtzite structure type with full Zn/Ge disorder, but was shown to be able to adopt an ordered β‐NaFeO 2 ‐type Wurtzite‐superstructure …”
Section: Introductionmentioning
confidence: 99%